What is the value of (-7 + 3i) - (2-6i)?
2 answers:
Answer:
9 (i - 1)
Step-by-step explanation:
Simplify the following:
-7 + 3 i - (-6 i + 2)
-(2 - 6 i) = -2 + 6 i:
6 i - 2 - 7 + 3 i
-2 + 6 i - 7 + 3 i = (6 i + 3 i) + (-2 - 7) = -9 + 9 i:
9 i - 9
Factor 9 out of 9 i - 9 giving 9 (i - 1):
Answer: 9 (i - 1)
Answer:
<h2>-9 + 9i</h2>
Step-by-step explanation:
![(-7+3i)-(2-6i)\\\\=-7+3i-2-(-6i)\\\\=(-7-2)+(3i+6i)\\\\=-9+9i](https://tex.z-dn.net/?f=%28-7%2B3i%29-%282-6i%29%5C%5C%5C%5C%3D-7%2B3i-2-%28-6i%29%5C%5C%5C%5C%3D%28-7-2%29%2B%283i%2B6i%29%5C%5C%5C%5C%3D-9%2B9i)
You might be interested in
1 because it can't be reflected over more than one line to be the same
Answer:
a c and d
Step-by-step explanation:
Based on my calculation i know for sure F
would equal 10
Answer:
205
Step-by-step explanation:
Answer: y =2x-5
Work:
2x-y=5
-y=-2x+5
-1y/-1 = -2x+5/-1
y =2x-5